Azizi Haji Abdullah Sebagai Seorang Novelis - Taib, Mohamad (Universiti Sains Malaysia, 1977)
This study centers around novelist Azizi Haji Abdullah. This paper is mainly based on. the organisational structure of four of his novels namely Garis Lintang Anak Haram,Senja Belum Berakhir, Sami Mekong and Bila Hujan Malam.It also considers how successful Azisi is as a novelist.For the purpose of simplicity this analysis is divided into six chapters.Chapter I, shows the background of the contemporary society in Peninsular Malaysia. It examines the political,economic, religious, cultural and social aspects of the society. These are the main sources of Azizi’s works.